The role of dsRNA A-to-I editing catalyzed by ADAR family enzymes in the pathogeneses - Wanqing Liu; Yufan Wu; Tong Zhang; Xiaobo Sun; Dean Guo; Zizhao Yang (RNA Biology)
The process of adenosine deaminase (ADAR)-catalyzed double-stranded RNA (dsRNA) Adenosine-to-Inosine (A-to-I) editing is essential for the correction of pathogenic mutagenesis, as well as the regulation of gene expression and protein function in mammals. The significance of dsRNA A-to-I editing in disease development and occurrence is explored using inferential statistics and cluster analyses to investigate the enzymes involved in dsRNA editing that can catalyze editing sites across multiple biomarkers. This editing process, which occurs in coding or non-coding regions, has the potential to activate abnormal signalling pathways that contributes to disease pathogenesis. Notably, the ADAR family enzymes play a crucial role in initiating the editing process. ADAR1 is upregulated in most diseases as an oncogene during tumorigenesis, whereas ADAR2 typically acts as a tumour suppressor. Furthermore, this review also provides an overview of small molecular inhibitors that disrupt the expression of ADAR enzymes. These inhibitors not only counteract tumorigenicity but also alleviate autoimmune disorders, neurological neurodegenerative symptoms, and metabolic diseases associated with aberrant dsRNA A-to-I editing processes. In summary, this comprehensive review offers detailed insights into the involvement of dsRNA A-to-I editing in disease pathogenesis and highlights the potential therapeutic roles for related small molecular inhibitors. These scientific findings will undoubtedly contribute to the advancement of personalized medicine based on dsRNA A-to-I editing.